Peningkatan Investasi Dan Hilirisasi Nikel Di Indonesia - Agung, Muhammad; Adi, Emmanuel Ariananto Waluyo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Indonesia is one of the countries that has the largest nickel reserves in the world. In addition to being used for export, currently the government has required domestic downstream nickel. In addition, the potential for nickel in Indonesia also plays a role in increasing investment for state revenues through investment consolidation. Through the policy of banning nickel ore exports, the long-term sustainability of raw nickel supply for domestic smelter needs is maintained. However, there are issues in the community due to the export ban affecting the selling price of nickel, in particular having an impact on business activities. This paper discusses the extent of nickel investment policies, nickel ore exports, downstreaming, and the obstacles faced. The author found that nickel downstreaming actually pushed nickel prices in a positive direction, thus encouraging investors to come to Indonesia